Pollination ecology and fruit development of Molineria rubriclavata and Molineria latifolia - Ismail, Mohd Firdaus (2014)
Molineria Colla is a perennial shrub that produced fruits containing a sweet protein called curculin. Observation in the wild populations across the peninsular showed that fruit set were inconsistent. Some plants produced inflorescence with complete fruit set and some did not. Undeveloped fruits were found in irregular number and pattern on the inflorescence. Plants transplanted and maintained under the rain shelter had poor performance in term of fruit setting even though flowers were produced abundantly. However, the lack of information on the basic aspect of the plant such as the pollination ecology hinders the effort to improve the fruit setting problems in a short time. Thus a study was carried out focusing on pollination ecology and fruit development of Molineria rubriclavata and Molineria latifolia var. megacarpa. Pollination ecology studies focused on flower anthesis, anther dehiscence, stigma receptivity and pollen viability. Anthesis was found to occur within one day. The flower normally started to open around 5.00 am in the morning. It was found that anthesis is heavily influenced by weather condition especially the sun light exposure period. The anthers dehisced before the flowers were open as early as 8.00 pm in the evening of the previous day of flower opening. However the stigma was fully receptive in the mid-morning around 6.00 am once the flowers were opened and started to dry up around 11.00 am. The pollen viability increased after 5 hours of anther dehiscence that started around 8.00 pm and peaked at 6-8 hours before decreasing gradually. The next study focused on identification of pollinators and pest of Molineria rubriclavata and Molineria latifolia and how the interactions affected fruit setting. Various types of insect were recorded visiting the Molineria flowers for various reasons. The main pollinators for Molineria were identified as the ants while the most efficient were the bees however the frequency of visitations by the ants were much higher than the bees thus they were ranked as the main pollinators. The common pest for Molineria rubriclavata and Molineria latifolia was the termite that could cause the whole plant to die. Snails were also found to forage on the flower especially the anthers. Polymorphism on flower structure was observed among Molineria varieties and species. Two varieties of Molineria latifolia were recorded to have heterostylous flowers. Three morphs of heterostylous flowers were found. Molineria latifolia var. megacarpa was the only species that contained all three flower morphs while Molineria latifolia var. rutilovenis have two flower morphs. The last parts of the research focused on flower and fruit development. Flower and inflorescence development were studied using microscopic techniques which were histology and Scanning Electron Microscopic. Whereas the fruit development studies were conducted to look at fruits development, fruit bunch development and also seed development. The investigations on fruit development showed that the fruits started to ripen 12 weeks after pollination while the seeds were fully developed around 6-8 weeks. In general, it can be concluded that the most suitable time for pollination of Molineria rubriclavata and Molineria latifolia is between 6.30 am to 10.00 am. The ecological factors that affect the anthesis were rain, mucilage and position of the flower. The main pollinators for this plant were ants namely Monomorium destructor, Meranoplus bicolor and Tapinoma sp. The visit of the pollinator was influenced by the size of the flower. Molineria latifolia produced heterostylous flower to increase the number of pollen in order to ensure higher pollination success in the absence of pollinator. The growth rate of fruit length and width were at the maximum at week 2 and week 3 after pollination respectively while fruit weight is at the highest at week 12. As for the seed, the maximum growth rate for length and width were both at week 2 after pollination. The seed fresh and dry weight highest growth occurred at week 3 after pollination.